The Zulu bow songs of Princess Magogo - Rycroft, David K. (International Library of African Music, 1975)
The Mntwana (Princess) Constance Magogo kaDinuzulu has for a great many years been recognised as the greatest living authority on Zulu music, besides being an expert performer without peer. Her vast repertoire of traditional Zulu songs extends back as far as the eighteenth century and she is herself a prolific composer. Her favourite instrument is the large ugubhu musical bow, used for self-accompanied singing, and she appears to be the last remaining player of this important historic instrument. She also plays the umakhweyana bow (with divided string) and, for music of a lighter style, the European autoharp.
Keywords: African Music